ECOLOGICAL ASPECTS OF METAZOAN PARASITES OF CALLICHIRUS SEILACHERI (BOTT 1955) (DECAPODA, CALLIANASSIDAE) FROM LIMA, PERU - Iannacone, Jose (2008)
Quantitative aspects of parasite communities of marine macrozoobenthonic crabs, as burrowing shrimpCallichirus seilacheri (Bott 1955) was not registered in South Pacific and Peru. For this reason, influence of size and sex of C. seilacheri, and evaluated period on its metazoan parasites was analyzed. Between November 1996 and January 2008, 1044 C. seilacheri acquired from Chorrillos, Lima, Peru, and necropsied to study their metazoan parasite. Of the burrowing shrimp collected, 571 were males and 473 females. Total length host mean was 10.62 ± 2.91 cm. Metazoan parasites were collected and registered employing standard procedures. Outer body surface, gill chamber, hemocoel, gut and hepatopancreas were examined. None parasite have three hundred forty and seven hosts. Showed infection with 1 parasite species, five hundred fifty and two hosts (52.9%), and with 2 parasite species forty-five had an infection (13.9%). Seven thousand seven hundred and fifty specimens in total during all the survey, with a mean abundance of 4.15 (1-67) were collected. The mean parasite species richness was 0.81 (1-2). Two parasites: Prochristianella hispida (Linton, 1890)(Cestoda) (hepatopancreas; prevalence = 32.8%; mean abundance = 0.92) and Clausidium vancouverense (Haddon, 1912) (Copepoda) (outer body surface and gill chamber; prevalence = 51.6%; mean abundance = 3.61) were survey. Abundance of infection of Parachristianella sp. and Clausidium vancouverense showed relation with size of C. seilacheri. Absence of association of size host with prevalence of infection of both parasites was found. Host sex only was found in dependence with prevalence of C. vancouverense. Prevalence and abundance of infection for both parasites showed variation during all period evaluated.